2009
DOI: 10.1007/s11547-009-0372-z
|View full text |Cite
|
Sign up to set email alerts
|

New guidelines on the use of iodinated contrast media: a report on an implementation project

Abstract: Purpose. The aim of this paper is to report on the implementation of new guidelines on the use of injectable iodinated contrast media (ICM) at our workplace and specific protocols for the preparation of patients at risk. Materials and methods. Operators received training with continuing medical education (CME) credits. The new documentation (patient history/screening form and informed consent form) is available on the hospital Web site and requests serum creatinine determination with estimation of glomerular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The findings of the current study indicate the need for optimising the practice related to ICM administration in risk patients. Previous results show that implementation of guidelines for ICM use is essential and feasible despite the challenges, such as increased workload and logistical difficulties in rescheduling the examinations to a date compatible with the patient’s condition and other planned examinations 18 . The reported workload directly related to the use of a written checklist is 2 min and 40 sec per patient (which includes explaining the questions to the patient) 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of the current study indicate the need for optimising the practice related to ICM administration in risk patients. Previous results show that implementation of guidelines for ICM use is essential and feasible despite the challenges, such as increased workload and logistical difficulties in rescheduling the examinations to a date compatible with the patient’s condition and other planned examinations 18 . The reported workload directly related to the use of a written checklist is 2 min and 40 sec per patient (which includes explaining the questions to the patient) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The reported workload directly related to the use of a written checklist is 2 min and 40 sec per patient (which includes explaining the questions to the patient) 19 . One unwanted consequence of implementing guidelines regarding thyroid‐related risk was a transient increase of requests for T3, T4 and TSH determinations not justified by the patients’ clinical situations 18 . Previous studies have found that implementing of guidelines included a concise checklist covering all risk factors can get positive reactions from both radiographers and radiologists 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations